Do bank independency and diversification affect bank failures in Europe?. Issue 3 (31st July 2019) - Mili, Mehdi; Khayati, Anis; Khouaja, Amira
Abstract : Purpose: Motivated by agency theory, this paper aims to explore the impact of bank diversification and bank independency on the likelihood of bank failure. The effects of corporate governance (ownership and board structures) are also examined. Design/methodology/approach: Logistic regressions are used to explore the role of corporate governance on bank failure risk. This sample covers 608 banks from eight European countries. Findings: The results suggest that the well-documented finding that diversification and bank independency may increase bank failure risk does not persist under strong corporate governance mechanism. Thus, to reduce the bank failure risk, diversification should be strongly monitored by the management to avoid excessive risk-taking by shareholders. Originality/value: The approach used in this study differs from that used in previous studies from certain perspectives. First, unlike most previous studies that focused on the relationship between bank performance and bank diversification, the impact of income and asset diversification on bank failure is tested. Also, the impact of a combined effect of diversification and corporate governance variables on bank failure is tested. This allows the control for different ownership and board variables as factors that would potentially affect the likelihood of bank failure.